Tandem occlusions in acute ischemic stroke: impact of antithrombotic medication and complementary heparin on clinical outcome and stent patency - Neuberger, Ulf; Moteva, Konstantina; Vollherbst, Dominik; Schönenberger, Silvia; Reiff, Tilman; Ringleb, Peter A.; Bendszus, Martin; Pfaff, Johannes; Möhlenbruch, Markus Alfred (Journal of neuroInterventional surgery, 2020)
Background and purpose Mechanical thrombectomy (MT) and acute carotid stenting (ACS) of patients with acute ischemic stroke due to tandem occlusions (TO) of the anterior circulation was proven to be safe and effective, but the implications of periprocedural antithrombotic medications are only known to a limited extent. - Methods We conducted a retrospective analysis of 162 consecutive patients who presented with TO and were treated with MT and ACS in our center. Patients initially either received dual antiplatelet therapy (DAT) or tirofiban periprocedurally. Some patients were also treated with unfractionated heparin. The frequency of intracranial hemorrhages (ICH), as well as the impact on clinical outcome and stent patency of different medical regimes, were evaluated using univariate tests and adjusted multivariate logistic regressions. - Results Patients who received supportive treatment with heparin had significantly higher occurrences of any (OR, 2.46; 95% CI, 1.15 to 5.28) and symptomatic ICH (OR, 3.71; 95% CI, 1.18 to 14.95). Additionally, these patients were less likely to have a moderate clinical outcome after 90 days (modified Rankin scale 0-3; OR, 0.33; 95% CI, 0.15 to 0.72), but were more likely to have a fatal outcome after 90 days (OR, 2.84; 95% CI 1.10 to 7.31). These findings persisted in patients who received both DAT and heparin, but not for patients who received both tirofiban and heparin. - Conclusion Supportive administration of heparin in patients with TO and treatment with MT and ACS should be carefully considered, especially in patients who primarily receive DAT.
Gesehen am 18.11.2020